Analyse d’erreurs d’utilisation des prépositions du français chez les étudiants troisième semestre de La section française - Melina Kartika Putri Duha; Abdul Ghofur (Universitas Negeri Semarang, 2024)
This research examines the analysis of errors in the use of French prepositions. The object of this research is the results of tests on the use of prepositions in French for semester 3 students. This research is limited to the use of prepositions de lieu. Data collection techniques in this study used 3 techniques, namely: preparation, application, and conclusion. This research aims to find the most dominant forms of errors in the use of prepositions and forms of errors. The results of this research indicate that there are 19 forms of errors in the use of French prepositions by semester 3 students. This study also shows that the most dominant form of error in the use of the preposition de lieu is the use of the preposition